2016
DOI: 10.1503/cmaj.160511
|View full text |Cite
|
Sign up to set email alerts
|

Association between day of the week of elective surgery and postoperative mortality

Abstract: BACKGROUND:In prior studies, higher mortality was observed among pa tients who had elective surgery on a Friday rather than earlier in the week. We investigated whether mortality af ter elective surgery was associated with day of the week of surgery in a Can adian population and whether the association was influenced by surgeon experience and volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…However, if this were true, one possible reason for these findings might be that, on a Friday, less experienced surgeons are operating on patients with less technically complex disease. This explanation seems supported by 2 previous studies showing that working experience among surgeons is lowest on Fridays, 16,17 with junior and midlevel surgeons performing more surgeries on Fridays and senior surgeons performing fewer. 16 When it is common to have less experienced surgeons working on a Friday, it is also likely that patients with less technically complex disease are scheduled for surgery on a Friday, and these patients also may have a lower risk for adverse events.…”
Section: Discussionmentioning
confidence: 60%
“…However, if this were true, one possible reason for these findings might be that, on a Friday, less experienced surgeons are operating on patients with less technically complex disease. This explanation seems supported by 2 previous studies showing that working experience among surgeons is lowest on Fridays, 16,17 with junior and midlevel surgeons performing more surgeries on Fridays and senior surgeons performing fewer. 16 When it is common to have less experienced surgeons working on a Friday, it is also likely that patients with less technically complex disease are scheduled for surgery on a Friday, and these patients also may have a lower risk for adverse events.…”
Section: Discussionmentioning
confidence: 60%
“…1, Supplemental Digital Content 1, http://links.lww.com/MLR/B514 , for details of the study selection process). These included 10 studies with a total of >6,685,970 elective surgery patients 3 , 13 , 22 , 25 31 and 19 studies with a total of >1,424,316 urgent/emergent surgery patients 8 – 12 , 32 45 (exact sample sizes not calculable as 2 studies did not specify the number of patients included in the pertinent analyses 29 , 34 ). Data from 13 elective surgery cohorts and 24 urgent/emergent surgery cohorts were analyzed as 6 studies 3 , 9 , 32 , 34 , 35 , 40 reported on >1 cohort meeting our inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…The 10 studies identified that reported on elective surgery patients had sample sizes ranging from 819 to 3,755,866 patients (Table 1 ). Eight of the studies were multicenter 3 , 13 , 22 , 25 27 , 29 , 31 and 2 were single center. 28 , 30 Four studies were conducted in Europe, 22 , 25 , 27 , 29 4 in North America, 13 , 28 , 30 , 31 1 in New Zealand, 26 and 1 included data from 4 countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent analyses of possible effectors on mortality could show that the day of the week, on which the procedure was performed, had a significant influence. A study on mortality after nonemergent surgery found an increased rate for procedures performed on fridays versus monday to wednesday [1] another one showed higher mortality rates in patients with elective colorectal resections being performed on fridays versus monday to thursday [2]. Also there is a cultural belief in more than ten percent of the Western European population, that the moon affects health care and is assumed to have a negative effect on procedures, as the occurrence of Friday 13 th is supposed to be associated with worsened outcome [3].…”
Section: Introductionmentioning
confidence: 99%